Service work in 2050: toward a work ecosystems perspective. (17th September 2018) - Subramony, Mahesh; Solnet, David; Groth, Markus; Yagil, Dana; Hartley, Nicole; Beomcheol Kim, Peter; Golubovskaya, Maria
Abstract : Purpose: The purpose of this paper is to explore the changing nature of the relationship between service workers and their work arrangements. Building upon classical and contemporary management theories and examining current trends and disruptions in employment relationships, it proposes a dynamic and relational model applicable to the management of service work in future decades (notionally in the year 2050). Design/methodology/approach: This paper introduces and develops the concept of worker–ecosystem relationship as a core construct to describe the participation and productivity of workers in the significantly transformed work environment of 2050. Findings: This paper argues that in work ecosystems – defined as relatively self-contained and self-adjusting systems – work arrangements will evolve toward less-clearly defined employment relationships characterized by long-term social contracts, tightly defined work roles and physical proximity of workers and organizations. Originality/value: A novel yet theoretically rooted construct of work ecosystems is introduced, using this new lens to predict changes in the nature of service work in 2050.